Toxicogenomic analysis of the pulmonary toxic effects of hexanal in F344 rat - Cho, Yoon; Lim, Jung-hee; Song, Mi-Kyung; Jeong, Seung-Chan; Lee, Kyuhong; Heo, Yongju; Kim, Tae Sung; Ryu, Jae-Chun (WILEY-BLACKWELL, 2017)
Hexanal is a major component of indoor air pollutants and is a kind of aldehydes; it has adverse effects on human health. We performed an in vivo inhalation study and transcriptomic analysis to determine the mode of toxic actions in response to hexanal. Fischer 344 rats of both sexes were exposed by inhalation to hexanal aerosol for 4 hday(-1), 5 daysweek(-1) for 4 weeks at 0, 600, 1000, and 1500 ppm. Throughout our microarray-based genome-wide expression analysis, we identified 56 differentially expressed genes in three doses of hexanal; among these genes, 11 genes showed dose-dependent expression patterns (10 downregulated and 1 upregulated, 1.5-fold, p<0.05). Through a comparative toxicogenomics database (CTD) analysis of 11 genes, we determined that five genes (CCL12, DDIT4, KLF2, CEBPD, and ADH6) are linked to diverse disease categories such as cancer, respiratory tract disease, and immune system disease. These diseases were previously known for being induced by volatile organic compounds (VOCs). Our data demonstrated that the hexanal-induced dose-dependent altered genes could be valuable quantitative biomarkers to predict hexanal exposure and to perform relative risk assessments, including pulmonary toxicity. (c) 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 382-396, 2017.
Keywords: INDOOR AIR-POLLUTION; HUMAN ALVEOLAR CELLS; GENE-EXPRESSION; INHALATION TOXICITY; PROINFLAMMATORY ACTIVATION; FISCHER-344 RATS; DRINKING-WATER; DOSE-RESPONSE; EXPOSURE; LUNG